Skin Tumors and Reactions to Cancer Therapy in Children (Springer International Publishing, 2018)
In today's era of genomic testing, targeted cancer therapies, and increased cancer survivorship, recognition and management of oncologic disease in children is becoming more important to address. This book familiarizes clinicians with the range of oncologic issues that pediatric dermatologists encounter, including the diagnosis and management of various skin tumors, cutaneous reactions to cancer therapies, and both acute and long term complications of cancer therapy. Written and edited by experts in the field, Pediatric Skin Tumors and Cutaneous Reactions to Cancer Therapy explores these important topics, beginning with the discussion of various skin tumors, and associated genetic syndromes, followed by chapters on acute cutaneous reactions to traditional and targeted cancer therapies, graft versus host disease, and opportunistic skin infections. This book concludes with the discussion of both malignant and nonmalignant late effects of the skin in childhood cancer survivors. .